Decision-making in Latin American family firms: a systematic review of the literature - Alex Javier Sanchez Pantaleon; Omer Cruz Caro; Marden Rigoberto Zumaeta Barrientos; Angela Agip Pilco (Universidad Ciencia y Tecnología, 2023)
A large number of the powerhouses of the world economy are family-owned. In Latin America, these generate jobs and contributions to the regional economy. The decision-making of these companies significantly determines their good performance and sustainability, so it is crucial to understand their causes, nature, and effects. The present investigation is of a mixed approach, not experimental; Through the systematic literature review, current production is studied in four principal databases. This paper offers a current look at the state of the literature on family business decision-making in the Latin American context. The main results show that the current literature has a very limited field of application and that, added to this, the heterogeneity in family firms should allow generalizations. It is necessary to broaden the methods and perspectives of study to address the subject.